Pengaruh Pemasaran Digital Berbasis Media Sosial terhadap Efektivitas Penjualan dan Jangkauan Pasar AR Snakehead Fish di Kotawaringin Barat - Rudiansyah, Rudiansyah; Swalaganata, Galandaru (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to evaluate the influence of social media-based digital marketing on the sales effectiveness and market reach of AR SnakeHead Fish in West Kotawaringin, Central Kalimantan Province. The method used is quantitative by collecting data through observation, interviews and questionnaires. The research population consisted of active and potential consumers in West Kotawaringin, with samples taken randomly. Data analysis was carried out using multiple linear regression with the help of SPSS software. The research results show that user interaction and posting frequency have a significant effect on sales effectiveness and market reach. Digital marketing via TikTok is able to increase sales and significantly expand the market reach of AR SnakeHead Fish in West Kotawaringin.